Food for fuel: The effect of the US biofuel mandate on poverty in India - Ujjayant Chakravorty; Marie-Hélène Hubert; Beyza Ural Marchand (Quantitative Economics, 2019)
More than 40% of US grain is used for energy due to the Renewable Fuel Mandate (RFS). There are no studies of the global distributional consequences of this purely domestic policy. Using micro-level survey data, we trace the effect of the RFS on world food prices and their impact on household level consumption and wage incomes in India. We first develop a partial equilibrium model to estimate the effect of the RFS on the price of selected food commodities-rice, wheat, corn, sugar, and meat and dairy, which together provide almost 70% of Indian food calories. Our model predicts that world prices for these commodities rise by 8-16% due to the RFS. We estimate the price pass-through to domestic Indian prices and the effect of the price shock on household welfare through consumption and wage incomes. Poor rural households suffer significant welfare losses due to higher prices of consumption goods, which are regressive. However, they benefit from a rise in wage incomes, mainly because most of them are employed in agriculture. Urban households also bear the higher cost of food, but do not see a concomitant rise in wages because only a small fraction of them work in food-related industries. Welfare losses are greater among urban households. However, more poor people in India live in villages, so rural poverty impacts are larger in magnitude. We estimate that the mandate leads to about 25 million new poor: 21 million in rural and 4 million in the urban population.
Keywords: 330; Biofuels; distributional effects; household welfare; renewable fuel standard; poverty